Assessment of the influence of a net cage fish culture on the water quality in Furnas reservoir, Brazil (Research, Society and Development, 2022)
Aquaculture is growing rapidly around the world. In Brazil, fish farming in net tanks has high potential due its large number of reservoirs. However, cultivable areas of tanks with a high fish density may be more susceptible to eutrophication compared to other production systems, and may impair the ecosystem where they are installed. Therefore, attention is needed to this type of system to avoid environmental impacts. The objective of this study was to evaluate the influence of a fish farming in net tanks on the water quality of the Furnas reservoir, Brazil. For physical-chemical analysis, water samples were collected monthly during two production cycles. The results were compared to the limits proposed by the environmental legislation for water bodies in Brazil. It was noted that nitrite and phosphate presented mean values higher than those allowed; however, these results were not associated with fish farming, and there is no influence on the water quality of the Furnas reservoir during the study period. Water quality in the reservoir may be influenced by other activities developed in its basin, such as livestock and intensive agriculture that use many fertilizers, released into the reservoir through runoff.